BrettPhos Ligand Supported Palladium‐Catalyzed CO Bond Formation through an Electronic Pathway of Reductive Elimination: Fluoroalkoxylation of Activated Aryl Halides. Issue 44 (18th September 2014) - Rangarajan, T. M.; Singh, Rajendra; Brahma, Raju; Devi, Kavita; Singh, Rishi Pal; Singh, R. P.; Prasad, Ashok K.
Abstract We report an unprecedented BrettPhos ligand supported Pd‐catalyzed CO bond‐forming reaction of activated aryl halides with primary fluoroalkyl alcohols. We demonstrate that the Phosphine ligand (BrettPhos) possesses the property of altering the mechanistic pathway of reductive elimination from nucleophile to nucleophile. The Pd/BrettPhos catalyst system facilitates the reductive elimination of the oxygen nucleophile through an electronic pathway.